1980
DOI: 10.1136/jmg.17.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Carrier detection in Duchenne muscular dystrophy.

Abstract: SUMMARY Serum creatine kinase, myoglobin, and percentage lymphocyte capping was determined in ten patients with Duchenne muscular dystrophy, 12 carriers (nine definite and three probable), 16 other female relatives, and eight normal controls. There was no detectable difference in lymphocyte capping ability between any of these clinical groups. Significant myoglobinaemia was present in all the affected males, but the difference in levels between carriers and controls suggested that this test has no advantage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The frequency of new mutants among patients with DMD ranges from 16.4% to 39.5% in Caucasians and Asians (Bucher, Ionasescu, & Hanson, 1980; Kong et al., 2019; Patiño, Narbona, & García‐Delgado, 1995), and is up to 62.2% in Latin Americans (Alcántara et al., 1999). In four of our carrier mothers, CK levels were above the normal range values, which means that the assay of CK activity may be a reliable and cost‐effective criterion to determine carrier status (Fitzsimmons et al., 1980; Hutton & Thompson, 1976), especially in sub‐Saharan African settings where molecular diagnosis facilities are not always available. The determination of carrier status is critical for the genetic counseling (Lane, Robinow, & Roses, 1983).…”
Section: Discussionmentioning
confidence: 95%
“…The frequency of new mutants among patients with DMD ranges from 16.4% to 39.5% in Caucasians and Asians (Bucher, Ionasescu, & Hanson, 1980; Kong et al., 2019; Patiño, Narbona, & García‐Delgado, 1995), and is up to 62.2% in Latin Americans (Alcántara et al., 1999). In four of our carrier mothers, CK levels were above the normal range values, which means that the assay of CK activity may be a reliable and cost‐effective criterion to determine carrier status (Fitzsimmons et al., 1980; Hutton & Thompson, 1976), especially in sub‐Saharan African settings where molecular diagnosis facilities are not always available. The determination of carrier status is critical for the genetic counseling (Lane, Robinow, & Roses, 1983).…”
Section: Discussionmentioning
confidence: 95%
“…Adornato et a1 [ 19781 first reported that some carriers of DMD had an elevated serum myoglobin (Mb) concentration and suggested that serum Mb and CK measurements in combination might identify a higher proportion of carriers than either CK or Mb alone. Subsequent surveys have confirmed that serum Mb is elevated in DMD carriers and also in carriers of Becker muscular dystrophy [Adornato et al, 1978;Ando et al, 1980;Fitzsimmons et al, 1980;Kagen et al, 1980;Konagaya et al, 1982;Miyoshi et al, 1978;Nicholson, 1981 ;Norregaard-Hansen and Hein-Sorensen, 1982;Norregaard-Hansen et al, 19781. It is not yet clear whether CK or Mb testing is more effective in DMD carrier detection, or whether there is any advantage in using the two tests in combination.…”
Section: Introductionmentioning
confidence: 80%
“…The full-field ERG of patients with DMD showed alterations in scotopic and photopic responses. 6,15,16,18,19,[22][23][24][25]43,[45][46][47][48][49][50] Indications of impairment in the visual pathways were also observed using visual evoked potential (VEP) techniques. Benoff et al 47 investigated the contrast sensitivity mediated by magno-and parvocellular pathways isolating the responses of the "ON" and "OFF" subsystems of the visual pathway.…”
Section: Discussionmentioning
confidence: 99%